ANALISIS PENGARUH DISPLAY PRODUK, PROMOSI BELOW THE LINE, DAN EMOSI POSITIF TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF PADA SRIRATU DEPARTEMENT STORE - Nugraheni, Rini; I’sana, Allan Dwi (Diponegoro Journal of Management, 2013)
Recently in  retail  market,  there was  a  phenomenom that  indicated  the marketdecrease. And then some company make a new strategy to adapt with the change of market. One of strategy was to increase the unplanned purchasing/impulse buying. Unplanned purchasing behavior (unplanned buying) or impulsive buying is something interesting for producers and retailers,because it’s a huge market share in the modern market. Then, the phenomenon of "impulse buying" is something that must be created. This study aims to: (1) analyze the effect of display products against impulsive buying decision. (2) analyze the influence of below the line promotion against impulsive buying decision. (3) analyze the effect of positive emotions on purchase decisions impulsively.This study was analyzed by using a multiple regression analysis/OLS (Ordinary Leeast Square) with SPSS. The data population was all Sri Ratu’s consumer. Than data sample was chosen by accindental sampling. The data analyzed by classical assumption and hypotesys test .In collecting the data, the study analyzed primary data generated from the distribution of questionnaires from 97 respondents that consumers who buy the product at Sri Ratu.The analysis showed that: (1) Display product has positive influence on impulsive purchasing decisions. (2) Below the line promotion has a positive influence on purchase decisions impulsively. (3) Positive emotions has positive influence on impulsive purchasing decisions.From this research, positive emotion has a most affected on impulse buying decision. So the company must attract consumen’s positive emotion that will increased the selling.